The assessment of the significance of social activities related to road safety at local and global level - Goniewicz, Krzysztof; Goniewicz, Mariusz; Pawłowski, Witold; Czerski, Robert (Journal of Education, Health and Sport, 2017)
The road accident problem is currently one of the most important issues in the health and social policies of states on all continents. Almost 1.3 million people die on the road every day, and 20-50 million people suffer severe injuries, most of which require long-term treatment. The aim of the study was to find the most frequent and permanent causes of road accidents and to present actions that should create the basis for the development of road safety strategies and programs at local and global levels. A comparative analysis of the literature on road safety shows that, although road accidents have the most common and often complex undertow, their causes have changed a little over the years. Strategies and programs to improve road safety should include the following actions: reducing exposure to accidents, preventing accidents, reducing injuries caused by accidents, reducing injuries by improving the accident medical care.